2021
DOI: 10.1029/2021gl093913
|View full text |Cite
|
Sign up to set email alerts
|

Energy Modulations of Magnetospheric Ions Induced by Foreshock Transient‐Driven Ultralow‐Frequency Waves

Abstract: Although foreshock transients can generate strong magnetospheric Pc5 ultralow-frequency (ULF) waves, whether they can modulate the energy of magnetospheric ions is still poorly understood.In this study, we analyze the strong magnetospheric ion energy modulations in a foreshock transient event on October 30, 2008, based on the magnetospheric observations by the time history of events and macroscale interactions during substorms A and D in the prenoon sector. ULF wave-induced  E B drift accelerated the cold ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 76 publications
1
25
0
1
Order By: Relevance
“…The resulting magnetosheath perturbations and the impact on the dayside magnetopause have been simulated (e.g., Lin and Wang, 2005;Omidi et al, 2016;Sibeck et al, 2021)) and observed (e.g., Archer et al, 2014;Jacobsen et al, 2009;Kajdičet al, 2021;Sibeck et al, 1999;2000). Similar to the impact of the solar wind dynamic pressure perturbations, the magnetopause distortion driven by foreshock transients can subsequently generate ultralow frequency (ULF) waves inside the magnetosphere (e.g., Hartinger et al, 2013;Wang et al, 2017;Wang et al, 2018b;Wang et al, 2019;Wang B. et al, 2020;Shi et al, 2021;Wang B. et al, 2021), enhance particle precipitation and the resulting aurora brightness (e.g., Fillingim et al, 2011;Wang et al, 2018a;Wang et al, 2018b;Wang et al, 2019), and enhance field-aligned currents (FACs) and the associated perturbations in ionospheric currents and ground magnetic field (e.g., Kataoka et al, 2002;Murr and Hughes, 2003;Fillingim et al, 2011;Shen et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The resulting magnetosheath perturbations and the impact on the dayside magnetopause have been simulated (e.g., Lin and Wang, 2005;Omidi et al, 2016;Sibeck et al, 2021)) and observed (e.g., Archer et al, 2014;Jacobsen et al, 2009;Kajdičet al, 2021;Sibeck et al, 1999;2000). Similar to the impact of the solar wind dynamic pressure perturbations, the magnetopause distortion driven by foreshock transients can subsequently generate ultralow frequency (ULF) waves inside the magnetosphere (e.g., Hartinger et al, 2013;Wang et al, 2017;Wang et al, 2018b;Wang et al, 2019;Wang B. et al, 2020;Shi et al, 2021;Wang B. et al, 2021), enhance particle precipitation and the resulting aurora brightness (e.g., Fillingim et al, 2011;Wang et al, 2018a;Wang et al, 2018b;Wang et al, 2019), and enhance field-aligned currents (FACs) and the associated perturbations in ionospheric currents and ground magnetic field (e.g., Kataoka et al, 2002;Murr and Hughes, 2003;Fillingim et al, 2011;Shen et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
“…Note that there are weak perturbations in the foreshock and the magnetosheath due to the foreshock ULF waves. The TD first encounters the foreshock ions just outside the dayside bow shock at t ∼44 min and foreshock transient perturbations are formed (see Wang B. et al (2021) for more details about the initiation of the foreshock transient).…”
Section: Magnetosheath Perturbations and Tailward Propagationmentioning
confidence: 99%
See 2 more Smart Citations
“…Стандартные способы наблюдения азимутальномелкомасштабных волн включают в себя искусственные спутники Земли и радары. Первые примеры волн с m>>1, наблюдаемых с помощью этих методов, были описаны в статьях [Cummings et al, 1969;Allan et al, 1982;Walker et al, 1982]. Применяются и другие методы изучения этих волн: с помощью пульсаций риометрического поглощения [Beharrell et al, 2010;Моисеев и др., 2020], по данным о полной электронной концентрации в ионосфере, полученным с помощью приемников GPS [Watson et al, 2016;Zhai et al, 2021], по оптическим данным [Motoba et al, 2015;Baddeley et al, 2017].…”
Section: рис 21 параметр τ как функция длины вдоль силовой линии Lunclassified